BALANCED NUTRITION EDUCATION AND NUTRITIONAL STATUS SCREENING OF MALE ADOLESCENTS IN DORMITORY - Junita, Dini; Fitri, Yulia; Suryana, Suryana; Mulyani, Nunung Sri (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2024)
Introduction: Adolescence is a golden period of reproductive, psychological and intelligence development. During the transition period between childhood and adulthood, biological, emotional, social and cognitive changes occur. Fulfilling nutrition during this period is important. This activity aims to educate teenagers about balanced nutrition and screen their nutritional status. Methods: This community service activity is carried out by providing education about balanced nutrition through lecture and discussion methods. While screening the nutritional status of adolescents is done through anthropometric measurements of body weight and height. The results of anthropometric measurements were then processed using the BMI formula according to age to obtain a z-score that describes the nutritional status of adolescents. This activity was carried out in dormitory of a high school with 36 young male participants. Results: Based on verbal observation and evaluation, students can receive and understand the material about balanced nutrition that is given properly. The results of the nutritional status screening showed that 31 of the adolescents in this activity (86%) had good nutrition but there were still students who had problems with thinness (3%), overweight (8%) and obesity(3%). Conclusion: It is recommended that schools and boarding schools follow up on students who are not in the good nutrition category. Students are directed to consume a balanced diet and physical activity so as to achieve the ideal body weight according to their height and age.